Semiconducting Perylene Diimide Nanostructure: Multifunctional Phototheranostic Nanoplatform - Yang, Zhen; Chen, Xiaoyuan (Accounts of chemical research, 2019)
Conspectus Precision medicine requires noninvasive and accurate early diagnosis and individually appropriate treatments. Phototheranostics has been considered a frontier precision medical technology to provide rapid and safe disease localization and efficient cure. Harnessing the power of advanced nanomedicine with photonics, phototheranostics is rapidly developing and progressively becoming irreplaceable in modern medicine. Nanoscale semiconducting materials, such as inorganic semiconductors, organic conjugated polymers, and small molecules with photonic properties, have been extensively explored in medical imaging (fluorescence imaging, optical coherence tomography, and photoacoustic [PA] imaging) and phototherapy (photothermal, photodynamic, and photocontrolled combination therapies). In practical clinical applications, organic semiconducting materials, because of their biocompatibility and natural metabolism, are preferred over inorganic materials for phototheranostics. Supramolecular self-assembly is considered a significant method for preparing organic detachable and multifunctional phototheranostics, as supramolecular interactions, such as π–π interactions, hydrogen bonding, hydrophobic effects, and electrostatic interactions, are non-covalent and dynamic. Developing new and effective organic supramolecular phototheranostics requires exploration of well-designed basic building blocks with optical properties, understanding of the assembly at the nanoscale, and optimization of the phototheranostics with unique and distinctive multifunctional efficacy. In this Account, we summarize our recent work on the development of small molecular semiconducting perylene diimide (SPDI) for advanced phototheranostics. SPDI is modified to have strong near-infrared absorption beyond 700 nm by the push–pull electronic effect and owns the merits of remarkable photostability, large extinction coefficient, and high photothermal conversion efficiency. By hydrophilic modification, the amphiphile can self-assemble into a nanomicellar structure that allows PA imaging and can serve as a photothermal conversion agent. After theranostics delivery is achieved, this SPDI can be further functionalized for multimodality imaging and photothermally triggered multimodal synergistic therapy. Several well-designed asymmetric structures of SPDI can be obtained by stepwise modification of imides. It is noteworthy that the self-assembly of SPDI is controllable, allowing the preparation of different-sized spherical nanoparticles and rodlike nanoparticles and nanodroplets. For biomedical applications of SPDI phototheranostics (SPDIPTs), the size effect of SPDIPTs has been highlighted in lymph node mapping and cancer imaging. The PA properties and targeting peptide modification of SPDIPTs have brought about the ultrasensitive imaging of early thrombus. The supramolecular nanoconstructs of SPDIPTs further permit multimodality-imaging-guided cancer therapy. In brief, the design of SPDIPTs considers synthetic chemistry, supramolecular self-assembly, nanotechnology, and photonics. Furthermore, SPDIPTs have diverse biomedical applications and offer many opportunities for advancing nanomedicine.